2014
DOI: 10.1111/jch.12333
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Variability and Morning Blood Pressure Surge in Elderly Chinese Hypertensive Patients

Abstract: 2This retrospective study aimed to investigate blood pressure variability (BPV), morning systolic blood pressure surge (MBPS), and the associated factors in 513 elderly (65 years and older) and 188 younger (younger than 65 years) hypertensive Chinese patients who had ambulatory blood pressure monitoring (ABPM) at our hospital from January 1, 2002, to December 31, 2010. The MBPS was lower in the younger patients compared with the elderly patients, and it was highest in the 75 years and older and younger than 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Qin et al used ABPM retrospectively to investigate BPV, EMBS, and associated factors in 513 elderly (≥65 years) and 188 younger (<65 years) Chinese patients with hypertension . The EMBS was lower in younger versus elderly patients, and was highest in those aged 75 to 80 years (29.0 ± 13.4 mm Hg).…”
Section: Evidence From Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…Qin et al used ABPM retrospectively to investigate BPV, EMBS, and associated factors in 513 elderly (≥65 years) and 188 younger (<65 years) Chinese patients with hypertension . The EMBS was lower in younger versus elderly patients, and was highest in those aged 75 to 80 years (29.0 ± 13.4 mm Hg).…”
Section: Evidence From Asiamentioning
confidence: 99%
“…Compared with other groups, patients aged ≥80 years showed significantly greater BPV ( P < 0.05). Multiple linear regression analysis showed that body mass index (BMI; P < 0.01), smoking history of up to 50 years ( P ≤ 0.03), and circadian BPV ( P < 0.01) were associated with EMBS . In a study of 340 patients from China, the proportion of subjects with EMBS was higher in patients with hypertension compared with normotensive participants .…”
Section: Evidence From Asiamentioning
confidence: 99%
“…Mancia et al concluded that BPV increased and heart rate variability decreased with age, but that changes in variability were not so obvious in hypertension [26]. In another report, Qin et al examined the BPV in elderly Chinese hypertension patients, they found that compared with other age groups, the group aged more than 80 years had a significantly increase in BPV (P \ 0.05) [27]. In Imai's study, age and mean BP were positively correlated with the ambulatory BPV evaluated with SD and CV indices [28].…”
Section: Discussionmentioning
confidence: 92%
“…Considerando a expressiva variabilidade da PA durante o dia em idosos 46 , os indícios aqui verificados reforçam a necessidade de novos estudos para se tecer conclusões mais efetivas e com fidedignidade, sobre o momento adequado para a realização do exercício resistido em idosos hipertensos.…”
Section: Análise Estatísticaunclassified